Apple Watch for Developers Advice & Techniques from Five Top Professionals - Riches, Gary.; Martinez, Ruben; Maison, Jamie; Klosterman, Matt.; Griffin, Mark.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2015)
Apple Watch for Developers: Advice & Techniques from 5 Top Professionals gives you the base-knowledge and valuable secrets you'll need for your own projects from a core team of successful, experienced Apple Watch app-development experts. You'll explore elements such as branding within Watch apps, translating audio data into visual information, taming complex data, mastering environment-driven feature sets, and much more. This book is for developers who already have some knowledge of developing with WatchKit and WatchOS 2, and who are now interested in learning how to use them to create cutting edge Watch apps. It is written by five experienced, industry-leading Apple Watch developers who have created their apps early, and are now ready to pull apart examples to show you how to best create an Apple Watch app. This book will bring your cool Watch ideas to life!
Keywords: Computer science; Computer Science; Computer Science, general; Electronic books